The occurrence of functional musculoskeletal disorders in young hockey players from the aspect of age in hockey - Kracek, S.; Grznárová, T.; Poór, O. (Zdravotnícke listy, 2019)
Background: In this work we focused on the occurrence of selected shortened and weakened muscles and their subsequent comparison between individual age categories. Objective: Our goal was to expand the knowledge of the occurrence of muscle imbalance from the aspect of age in hockey. Sample and methods: The main method of obtaining the data was Janda´s (2004) muscle-functional test. Our sample consisted of 63 ice hockey players from hockey pre-preparation (grades 0, 1st and 2nd grades of primary school, 3-8 years old; n = 22), hockey preparation (3rd and 4th grades of primary school, 8-10 years old; n = 29) and younger pupils (5th and 6th grades of primary school, 10-12 years old; n = 12). The average age of probands was 7.78 ± 2.08 years. Results: At the m. iliopsoas right (non-dominant) side there was proven significant difference at 5 % level (U = 171; p = 0.003) between the pre-preparational group and the preparational group, with the higher decrease in percentage in the preparation group. On the dominant side m. iliopsoas a significant difference at the 5% level of significance (U = 193.5; p = 0.010) between the pre-preparation group and the preparation group was observed with iliopsoas, with the higher decrease in percentage in the preparational group. We also noted a significant difference at 5 % level of significance (U = 69.0; p = 0.015) between pre-preparational group and younger pupils, witha higher decrease in percentage in the group of younger pupils. When compared the knee flexor of the right (non-dominant) side, we came to a statistically significant difference between the preparational group and the younger pupils at the 5 % significance level (U = 106.0; p = 0.032), with a higher shortening in the younger pupils group. In the left (dominant) side knee flexors, we noted significant differences at 5 % level between the preparational group and younger pupils (U = 101.5; p = 0.027), with younger pupils achieving a higher decrease in percentage. Another significant difference was between pre-preparational group and younger pupils (U = 77.5; p = 0.026), with younger pupils again having a higher decrease. There were no statistically significant differences in the other monitored muscles. Conclusion: Based on the results, we have shown a growing incidence of muscle imbalance from the youngest age categories to the older. Laterality between the dominant and non-dominant sides was also demonstrated.